Arabidopsis ORGAN SIZE RELATED1 regulates organ growth and final organ size in orchestration with ARGOS and ARL - Feng, Guanping (The New phytologist, 2011)
© 2011 The Authors. New Phytologist © 2011 New Phytologist Trust.